Highly sensitive strain sensing using a polarization-maintaining photonic crystal fibre based Mach–Zehnder interferometer. Issue 4 (23rd February 2022) - Zhang, Wujun; Wu, Xuqiang; Li, Shili; Yu, Guofeng; Shi, Jinhui; Gui, Lei; Ren, Bo; Zuo, Cheng; Yu, Benli
Abstract : A novel all-fibre highly sensitive strain sensor based on polarization-maintaining photonic crystal fibre (PMPCF) is proposed and demonstrated experimentally. The sensing structure is formed by splicing a segment of PMPCF between two segments of thin core fibres (TCFs). Since the responses of the resonance dips induced by different order cladding modes interference with core mode are different, the strain sensitivity can be obtained by monitoring the shifts of the resonance dips. The experimental results show that the sensitivity of strain of the MZI is 4.03 pm/µϵ within the strain range from 0 µϵ to 1600 µϵ, respectively. And the temperature characteristics are also researched. This type of sensor has outstanding advantages of convenient manufacture, high-cost efficiency and insensitivity to temperature, so it has potential application prospects in physical, biological and chemical sensing.